Online Assessment and Evaluation Tool in a Professional Institution-A Case Study - Murthy, A. V. S. (Journal of Engineering Education Transformations, 2008)
In today's competitive environment, the role of a teacher is changing. It is important for teaching fraternity to have a vision of their roles and responsibilities to provide the best teaching strategies for their students.